Outdoor learning in improving understanding of Brahmawihara materials among children at Buddhist sunday school - Nungki Ayu Febriyanti; Taridi Taridi; Dedi Kundana (Universitas Sebelas Maret, 2025)
This research aims to test the effectiveness of outdoor learning-based education in increasing the understanding of Sunday School children about the values of Brahmawihara (Metta, Karuna, Mudita, Upekkha). This study also emphasises the importance of enjoyable and contextual learning approaches to enhance children's engagement in understanding spiritual values. The method used is a one-group pretest-posttest design involving 20 children aged 10-12 years from two Buddhist Sunday Schools in East Lampung. Data collection was carried out through a multiple-choice test that has been tested for validity and reliability of 0.967, and was then analysed using paired sample T-test and one sample T-test. This supports the theory of experiential learning, with research results showing a significant increase in participant understanding, where the average pretest score was 60.20 SD=9.12, increasing to 86.30 SD=7.54 in the posttest. Statistical analysis reinforces these findings (t = -20.985, p = 0.000), with 85.71% of participants achieving the minimum learning completeness (KKM) ≥75. Activities such as nature meditation and role-playing proved to help children connect the values of Brahmawihara with their daily lives, strengthening the internalisation of these four noble qualities. Based on the research findings, it can be concluded that outdoor learning-based education is effective as an alternative method for teaching Brahmawihara to children in Buddhist Sunday school. The practical implication is that this approach can be integrated into the curriculum by taking into account the availability of supporting facilities and teacher training to ensure optimal implementation. For further research, it is recommended to broaden the sample scope by involving different age groups or locations with more diverse environmental characteristics to test the generalisation of findings in providing education to children. This study makes an important contribution to the development of interactive and contextual Buddhist education methods, especially in instilling noble values in Sunday School children.